Nesfatin-1 and Ghrelin/GOAT as Potential Biomarkers in Adolescent Headache with Temporomandibular Disorders: A Cross-Sectional Study - Sojka, Anna; Dorocka-Bobkowska, Barbara; Bartosik, Yasmin; Yetkin, Ozgun; Steinborn, Barbara; Żarowski, Marcin (Journal of Medical Science, 2025)
Introduction. Nesfatin-1 and Ghrelin O-acetyltransferase (GOAT) are peptide hormones involved in stress response and pain modulation beyond their metabolic functions. This study investigated whether these biomarkers differ between adolescents with headaches and healthy controls and examined their relationship with temporomandibular disorders (TMD). Material and methods. This cross-sectional study measured Nesfatin-1 and Ghrelin/GOAT levels in the serum and saliva of 44 adolescents with headaches (aged 10-17 years, diagnosed per ICHD-3 beta criteria) and 20 age-matched healthy controls. TMD was assessed using the Diagnostic Criteria for TMD (DC/TMD). Statistical comparisons were performed using non-parametric tests, with significance set at p < 0.05. Results. Nesfatin-1 was elevated in all headache patients compared to controls in both blood (patient median range: 39.5-45.0 ng/mL vs. control median range: 8.1-9.0 ng/mL, p<0.001) and saliva (patient median range: 6.6-8.2 ng/mL vs. control median range: 1.8-2.3 ng/mL, p<0.001) regardless of headache type (migraine vs. tension-type) or TMD status. Ghrelin/GOAT showed opposite patterns in blood versus saliva: serum levels were higher in patients (median range: 5.9-6.6 ng/mL vs. 1.4 ng/mL in controls, p<0.001), while salivary levels were lower (median range: 0.2 ng/mL vs. 1.4 ng/mL in controls, p<0.001). Gender differences emerged in clinical manifestations: females had more muscle pain (74% vs 38%, p = 0.016), while males reported more psychological distress (90% vs 48%, p = 0.003). Conclusions. This study reveals altered Nesfatin-1 and Ghrelin/GOAT levels in adolescents with headaches, independent of headache type or TMD status. These findings suggest potential utility as pain-related biomarkers, though validation studies with larger sample sizes and receiver operating characteristic analyses are needed before clinical implementation. Gender specific clinical patterns underscore the importance of sex-stratified approaches in adolescent pain management.